Determination of the production and sediment transport in the high river basin of the Yaque River of the North and the Guanajuma River, Dominican Republic - Cuello Espinosa, Maldane (2003)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2003